MODEL PELATIHAN GURU ILMU PENGETAHUAN SOSIAL DI SMP MUHAMMADIYAH KARTASURA - Subadi, Tjipto; Dahroni, Dahroni (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
The study aimed to review and describe: 1) Coaching model of social sciences teacher in SMP Muhammadiyah Kartasura. 2) Test the validation of coaching model on social sciences teacher. This study used a qualitative approach of phenomenology. This study was conducted in SMP Muhammadiyah Kartasura, Sukoharjo district. The research design was classroom action research. The subject in this research were students, teachers, the principal. Data collection technique used observation, testing and interview. The interview process using theory of first and second order understanding. Data were analyzed using an interactive model included data reduction, data display, and conclusion. This study concluded that 1) Coaching Model of social sciences teacher in SMP Muhammadiyah Kartasura used modification lesson study approach. 2) Validation of the coaching model using two kinds of validation namely theory of validation and practice of validation.